A financeirização do mercado imobiliário e seus reflexos na produção do espaço urbano: o caso de Salvador–BA (2005– 2022) - Santos, André Luís Cardoso (2023)
This thesis deals with the consequences of the financialization of the real estate market on the production of urban space and aims to analyze the results of this process in the urban space of Salvador – BA. From the 1980s onwards, Brazil went through profound political and economic changes with implications for the production paradigms of urban space in its cities, including the city of Salvador-BA, with the emergence of neoliberal policies and the financialization of a significant portion of production. real estate. Among the changes that have occurred there is the emergence of the City Statute and its instruments, the creation of the Real Estate Financial System and the opening of capital of a portion of large national construction companies and developers, which now have the participation of foreign capital in their corporate composition. Among the operating strategies of these companies that had implications for the dynamics of urban space production are the geographical expansion of the area of activity and the formation of extensive land banks in the main urban sectors of the country's main cities. In association, the State, through Master Plans and physical infrastructure interventions, provided a favorable environment for companies to operate and value developments. The survey of construction/developing companies that went public on the Brazilian Stock Exchange (B3) and that operated in Salvador made it possible to identify the projects carried out by these companies, the operating strategies in the urban space of Salvador and the practical results of this action. The results of the studies developed support the thesis that the financialization of the real estate market, via the opening of capital of construction/developing companies, allowed the direct participation of financial capital (including international capital) in the extraction of income from urban land with the support of State (via adaptation of instruments and guidelines for regulating the production of urban space). The activities of these companies resulted in the implementation of a myriad of enterprises dispersed throughout almost the entire municipal territory, with some areas showing a special concentration of these enterprises, areas that have become new urban centers, leading to an urban restructuring of the city.